A non-surgical management of delayed diagnosis of an oesophageal perforation due to ingestion of okra: A case report - Ismail R.; Mahamad U.A.; Marwan A.A. (Universiti Putra Malaysia Press, 2024)
Indexed by Scopus/MyCite